Melanoma and LEOPARD Syndrome: Understanding the Role of PTPN11 Mutations in Melanomagenesis - Rodolfo David Palacios-Diaz; Mónica Pozuelo-Ruiz; Blanca de Unamuno-Bustos; Margarita Llavador-Ros; Rafael Botella-Estrada (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)